2007
DOI: 10.13031/2013.24105
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Irrigation Management Using Multispectral Crop Coefficients: I. Crop Evapotranspiration Prediction

Abstract: A method widely used for irrigation management determines crop evapotranspiration (ET c) from reference evapotranspiration (ET o) calculations and estimated crop coefficients. However, standard time-based crop coefficients may fail to represent the actual crop water use, for example, when deviations in weather or agronomic constraints appreciably change crop development patterns from typical conditions. In this study, the FAO-56 dual crop coefficient procedures were applied during experiments with wheat to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 20 publications
(38 reference statements)
1
53
0
1
Order By: Relevance
“…Kcb NDVI values for the development growth stage ranged between 0.25 and 0.91 (Table 6), which refer to values commonly accepted [1]. The actual Kcb mid NDVI = 0.87 (Table 6) is lower than the standard Kcb = 1.10 proposed by Allen et al [1] and values obtained for crops with similar canopy [30,31,61]. This is likely due to different vegetation conditions in the 2012/2013 crop season and to the adjustment to climate [35].…”
Section: Estimation Of Actual Kcb From Reflectance-based Vegetation Imentioning
confidence: 58%
“…Kcb NDVI values for the development growth stage ranged between 0.25 and 0.91 (Table 6), which refer to values commonly accepted [1]. The actual Kcb mid NDVI = 0.87 (Table 6) is lower than the standard Kcb = 1.10 proposed by Allen et al [1] and values obtained for crops with similar canopy [30,31,61]. This is likely due to different vegetation conditions in the 2012/2013 crop season and to the adjustment to climate [35].…”
Section: Estimation Of Actual Kcb From Reflectance-based Vegetation Imentioning
confidence: 58%
“…Properly calibrated, Equation 1 can predict crop ET actual . For example, Hunsaker et al [4] found that wheat ET actual predicted from ET o and NDVI was within 5% of values determined in a weighing lysimeter. Gonzalez-Dugo et al [6] compared a VI/crop coefficient remote sensing method for estimating ET actual of corn and soybean crops in central Iowa, US, with three Surface Energy Balance (SEB) methods that utilized thermal bands, and reported root mean square differences of 0.4 mm d −1 for the VI/crop coefficient method and 0.4-0.6 mm d −1 for SEB methods when compared to moisture flux tower measurements.…”
Section: The Vegetation Index Approach For Scaling Et By Remote Sensingmentioning
confidence: 89%
“…Recent studies have combined ground measurements of evapotranspiration (ET), meteorological variables, and vegetation indices (VIs) determined by satellite sensors to project plant water use over diverse biomes, including deserts [1,2], semiarid rangelands [3], agricultural districts [4][5][6], riparian corridors [7,8], rainforests [9], and mixed landscape units at regional [10,11] and global [12,13] scales of measurement. Unlike remote sensing methods based on thermal (NIR) bands on Landsat or other high-resolution satellites, which provide a snap-shot of actual ET (ET actual ) at the time of satellite overpass [14,15], VI methods are useful in projecting ET actual over longer time periods (weeks, months and years), due to the modulated response of VIs to environmental conditions.…”
Section: The Vegetation Index Approach For Scaling Et By Remote Sensingmentioning
confidence: 99%
“…The single K c approach is basically indicated to irrigation planning and design and the dual K c approach is recommended for real time irrigation scheduling. This second approach has been also extensively evaluated (Allen, 2000;Suleiman et al, 2007;Hunsaker et al, 2007).…”
Section: Water Requirements For South American Cropsmentioning
confidence: 99%